Feasibility Study of Developing Rumah Galuh village in Local Tourism Development - Solahuddin Nasution; Ronald Leonardo Siregar (Budapest International Research and Critics University, 2021)
This study aims to describe a feasibility study for the development of the Rumah Galuh tourist village as a natural tourist destination in Langkat Regency, and a marketing solution for the Rumah Galuh village as a tourist destination. The method used in this research is descriptive qualitative method. Data collection techniques are the most strategic step in research, because the main purpose of research is to obtain data. Data collection techniques used in this study include: Field researchers. The theoretical framework used is a tourism feasibility study approach that includes several specific things that must be well understood if a tourism business is to maximize its potential for success. These include factors that affect the demand and supply of tourism. In fact, the potential demand for tourism products can be estimated, such as the number of residents around the area and the level of population density. Rumah Galuh Village is very suitable to be developed into a tourist village, where a village is said to be a tourism village is a form of integration between action, accommodation, and supporting facilities provided. In a structure of community life that blends with the prevailing procedures and traditions. Written in presentation materials at international conferences or proceedings, this also aims to improve research publications in the University of North Sumatra Environment regarding Environmental Management.